HUMAN RESOURCE CAPACITY IN PROCUREMENT GOVERNANCE BASED ON IMPORTANCE PERFORMANCE ANALYSIS (IPA) AT THE PROCUREMENT SERVICE UNIT OF GORONTALO PROVINCE - RACHMAT USMAN; Sri Nipsa Amrain; Azis Rachman; Nur Fatimahtuzzahro Putri S Kaharu (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to analyze human resource (HR) capacity in procurement governance at the Procurement Service Unit (PBJ) of Gorontalo Province using the Importance Performance Analysis (IPA) approach within a qualitative research framework. The study is motivated by the critical role of HR in ensuring the effectiveness, efficiency, transparency, and accountability of public procurement, as well as the existing gap between the level of importance and performance across several strategic aspects. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving informants such as procurement officials, working groups (Pokja), and procurement administrators. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, which was integrated with Importance Performance Analysis (IPA) to identify gaps between perceived importance and actual performance. The findings indicate that HR capacity within the PBJ unit is generally adequate and capable of supporting procurement implementation in accordance with prevailing regulations, particularly through the utilization of e-procurement systems. However, gaps remain in terms of the number of personnel, workload distribution, and the strengthening of integrity and technical capacity. The IPA results reveal that these aspects fall within the high-priority quadrant, requiring focused policy intervention